PENGARUH BUDAYA SELEBRITI TERHADAP PEMBENTUKAN IDENTITAS KARAKTER UTAMA DALAM NOVEL BERJUDUL 'ON A NIGHT LIKE THIS' KARYA LINDSEY KELK - Melvin Zefanya Neman; Isnawati Lydia Wantasen; Garryn Christian Ranuntu (An Nafi': Multidisciplinary Science, 2026)
This research, entitled “The Influence of Celebrity Culture on the Identity Formation of the Main Character in the Novel ‘On a Night Like This’ by Lindsey Kelk,” aims to analyze the protagonist's identity transformation. The study has two primary objectives: first, to identify Fran Cooper's initial identity characteristics before her exposure to celebrity culture, and second, to examine how celebrity culture influences her identity formation through the mechanisms of social categorization and social comparison. Employing a qualitative method with descriptive analysis, the data was collected through close reading and selection of relevant excerpts from the novel. The theoretical framework of Social Identity Theory by Tajfel and Turner (1979) is applied to guide the analysis. The findings reveal that Fran's identity evolution occurs through three distinct stages: Social Categorization, where she defines her in-group and out-group; Social Identification, where she adopts the norms of her new group; and Social Comparison, where she measures herself against celebrities, leading to a significant shift in her self-perception. This research concludes that celebrity culture acts as a powerful catalyst in the reformation of Fran Cooper's identity.